Identification, biosynthesis, and decapping of NAD-capped RNAs in B. subtilis - Frindert, Jens; Zhang, Yaqing; Nübel, Gabriele; Hotz-Wagenblatt, Agnes; Burhenne, Jürgen; Haefeli, Walter E.; Jäschke, Andres (Cell reports, 2018)
Summary - The ubiquitous coenzyme nicotinamide adenine dinucleotide (NAD) decorates various RNAs in different organisms. In the proteobacterium Escherichia coli, the NAD-cap confers stability against RNA degradation. To date, NAD-RNAs have not been identified in any other bacterial microorganism. Here, we report the identification of NAD-RNA in the firmicute Bacillus subtilis. In the late exponential growth phase, predominantly mRNAs are NAD modified. NAD is incorporated de novo into RNA by the cellular RNA polymerase using non-canonical transcription initiation. The incorporation efficiency depends on the −1 position of the promoter but is independent of sigma factors or mutations in the rifampicin binding pocket. RNA pyrophosphohydrolase BsRppH is found to decap NAD-RNA. In vitro, the decapping activity is facilitated by manganese ions and single-stranded RNA 5′ ends. Depletion of BsRppH influences the gene expression of ∼13% of transcripts in B. subtilis. The NAD-cap stabilizes RNA against 5′-to-3′-exonucleolytic decay by RNase J1.